2012
DOI: 10.1111/j.1753-4887.2012.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: an overview of its role in skeletal muscle physiology in children and adolescents

Abstract: Many children may have insufficient serum concentrations of vitamin D, which could prevent optimal muscle development and function. Vitamin D deficiency in animal models results in negative effects on muscle fiber structure and calcium/phosphorus handling, suggesting an integral role of vitamin D in skeletal muscle function. While there is a dearth of data in humans, the available evidence demonstrates a positive association between vitamin D status and muscle function. This review focuses on the important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 157 publications
(209 reference statements)
1
32
1
2
Order By: Relevance
“…Human studies assessing vitamin D deficiencies in youth have shown impaired motor function and development [135]. For example, in type I vitamin D resistant rickets distinct muscle weakness and delayed growth are present [135]. These patients are unable to convert vitamin D into its metabolically active form because of a mutation in the renal enzyme 25OHD-1-α-hydroxylase [135].…”
Section: Vitamin D and Muscle Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human studies assessing vitamin D deficiencies in youth have shown impaired motor function and development [135]. For example, in type I vitamin D resistant rickets distinct muscle weakness and delayed growth are present [135]. These patients are unable to convert vitamin D into its metabolically active form because of a mutation in the renal enzyme 25OHD-1-α-hydroxylase [135].…”
Section: Vitamin D and Muscle Interactionmentioning
confidence: 99%
“…For example, in type I vitamin D resistant rickets distinct muscle weakness and delayed growth are present [135]. These patients are unable to convert vitamin D into its metabolically active form because of a mutation in the renal enzyme 25OHD-1-α-hydroxylase [135]. In these children, muscle weakness is readily reversed following supplementation with 1,25(OH) 2 D, proving that this form of vitamin D is essential to adequate muscle function and development [135].…”
Section: Vitamin D and Muscle Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic vitamin D deficiency in adults results in osteomalacia, osteoporosis, muscle weakness. [1][2][3][4][5][6][7] Recent researches had also linked vitamin D deficiency with the increased risk of developing tuberculosis, otitis media, upper respiratory tract infections and influenza and many other infections. [8][9][10][11][12] Its deficiency has also linked with the increased risk of developing hypertension, diabetes, obesity and high triglyceride level ultimately leading to increased risk of cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%
“…(5) Therefore, an adequate intake of vitamin D during childhood and adolescence is necessary to enhance intestinal calcium absorption and ensure normal bone mineralization. (5) Several trials have investigated means to maximize peak bone mass through lifestyle measures, by increasing physical activity or emphasizing on dairy products consumption or supplementation of calcium and vitamin D. (1,(6)(7)(8)(9) Two randomized trials using calcium-fortified milk demonstrated increments in bone mass in adolescent Chinese girls and Gambian boys, but could not demonstrate residual effect after trial completion. (10,11) Our group had previously reported on the beneficial effects of vitamin D supplementation in adolescent girls, (12) but not boys, (13) on bone mineral content (BMC), bone mineral density (BMD), and lean mass, in a 1-year trial that compared two doses of vitamin D (low dose ¼ 200 IU/day; high dose ¼ 2000 IU/day) to placebo.…”
Section: Introductionmentioning
confidence: 99%